2009
DOI: 10.1002/jctb.2210
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of carvacrol by Friedel–Crafts alkylation of o‐cresol with isopropanol using superacidic catalyst UDCaT‐5

Abstract: BACKGROUND: Alkylation of o-cresol with propylene or isopropyl alcohol (IPA) over solid acid catalysts results in the formation of carvacrol, which finds potential applications in the synthesis of fine chemicals, intermediates, specialty chemicals, flavours and fragrances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…The drastic decrease in the overall ether selectivity at high conversion is most likely due to the fast ether decomposition mentioned above. However, for a given conversion level, this selectivity increases with the isopropanol/m‐cresol ratio, in agreement with the trends reported for the alkylation of m‐cresol and o‐cresol with isopropanol and tert ‐butanol . As shown in Figure , using propylene as alkylating agent instead of isopropanol, at the same C3/m‐cresol ratio and same level of conversion, results in a much lower selectivity toward ethers.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The drastic decrease in the overall ether selectivity at high conversion is most likely due to the fast ether decomposition mentioned above. However, for a given conversion level, this selectivity increases with the isopropanol/m‐cresol ratio, in agreement with the trends reported for the alkylation of m‐cresol and o‐cresol with isopropanol and tert ‐butanol . As shown in Figure , using propylene as alkylating agent instead of isopropanol, at the same C3/m‐cresol ratio and same level of conversion, results in a much lower selectivity toward ethers.…”
Section: Resultssupporting
confidence: 88%
“…Accordingly, the first step is the dehydration of the alcohol. From our experiments and previous studies, it was observed that dehydration of isopropanol can occur via two parallel paths, one is the direct dehydration and the other via formation of di‐isopropyl ether, which can further decompose to propylene and water IsopropanolPropylene + Water IsopropanolDiisopropyl ether + Water Diisopropyl etherPropylene + Water …”
Section: Resultssupporting
confidence: 59%
“…bergamia Loisel), and other plants (Fachini‐Queiroz et al, ; Kintzios, ; Lisin, Safiyev, & Craker, ; Tang, Chen, & Wang, ). Commercial CV is synthesized by chemical and biotechnological methods (Yadav & Kamble, ). It is also named 5‐isopropyl‐2‐methylphenol by the International Union of Pure and Applied Chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…It is also named 5‐isopropyl‐2‐methylphenol by the International Union of Pure and Applied Chemistry. Carvacrol has lipophilic properties and a density of 0.976 g/ml at room temperature (25 °C); it is insoluble in water but highly soluble in ethanol, acetone, and diethyl ether (Yadav & Kamble, ). As recently reviewed by several authors (Baser, ; Suntres, Coccimiglio, & Alipour, ), this compound possesses a wide range of biological activities, including antibacterial and antifungal (Chavan & Tupe, ; Du et al, ; Nostro et al, ), antiviral (Gilling, Kitajima, Torrey, & Bright, ; Sánchez, Aznar, & Sánchez, ), antioxidant (Aristatile, Al‐Numair, Al‐Assaf, & Pugalendi, ; Guimarães et al, ; Milos & Makota, ), and anticarcinogenic properties (Arunasree, ; Ozkan & Erdogan, ; Q. H. Yin et al, ; Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Carvacrol is highly lipophilic; the solubility of carvacrol is very high in carbon tetrachloride, ethanol, diethyl ether, acetone; but insoluble in water (Ultee et al, 2000). Yadav and Kamble (2009) reported that formation of carvacrol could be resulted from alkylation of o-cresol with propylene or isopropyl alcohol (IPA) over solid acid catalysts.…”
Section: Chemical and Physical Characteristicsmentioning
confidence: 99%